Spatial Planning of Mosque-Based Ablution Water Reuse Networks in Lombok Barat Using K-Means Clustering and Minimum Spanning Tree - Sutanto, Sutanto; Vulandari, Retno Tri; Nareswari, Tyas Titah (Universitas Negeri Gorontalo, 2026)
Lombok Barat Regency, located on Lombok Island, frequently experiences water scarcity due to its semi-arid climate and prolonged dry seasons. Agricultural and plantation activities in this region rely heavily on limited freshwater resources, particularly in dryland areas. Meanwhile, mosques continuously generate relatively clean greywater from daily ablution (wudu) activities. Despite its regular availability and relatively low contamination level, this resource remains largely underutilized. This study examines the spatial planning of mosque-based wudu water collection networks in West Lombok as a potential supplementary water source for plantation and dryland irrigation. A spatial analytical framework combining K-Means clustering and the Minimum Spanning Tree (MST) algorithm was applied and implemented through an interactive RShiny application. Spatial data from 940 mosques were preprocessed and analyzed. K-Means clustering at Level 1 grouped mosques into 25 local service clusters, while Level 2 clustering aggregated these clusters into five main reservoir zones. A cost-weighted MST based on Haversine distance was then used to estimate the minimum pipeline length required to connect mosques within the proposed network configuration. The results show that the modeled network connects all 940 mosques with a minimum total pipeline length of 411,757.28 meters and could potentially collect approximately 282,000 liters of reusable wudu water per day. However, the model represents a preliminary spatial planning framework and does not include hydraulic simulations, water quality validation, treatment system design, or operational feasibility assessment.